Polystyrene-Supported p-Toluenesulfonic Acid: A New, Highly Efficient, and Recyclable Catalyst for the Synthesis of Hydropyridine Derivatives under Solvent-Free Conditions - Reddy, Mudumala Veeranarayana; Jeong, Yeon Tae (Synlett, 2012)
A new environmentally benign method for the preparation of hydropyridine derivatives has been developed by a simple one-pot condensation reaction of dimidine, active methylene compounds with aldehydes, and ammonium acetate in the presence of polystyrene-supported p-toluenesulfonic acid as a highly active and reusable heterogeneous acid catalyst under solvent-free conditions at 60 °C. This new protocol has the advantages of easy availability, stability, reusability, and eco-friendliness of the catalyst, high to excellent yields, simple and easy experimental workup procedure.
Keywords: polystyrene-supported p-toluenesulfonic acid; hydropyridine derivatives; active methylene compounds; solvent-free conditions